Synergistic Effect of Solid State Hydrogen and Cold Work Pretreatment on Oxide Films Grown on 316L Stainless Steel during Short Term Immersion in Deaerated High Temperature Water at 300 °C. Issue 16 (25th November 2020) - Cui, Tongming; Ma, Jiarong; Zhang, Kun; Lu, Zhanpeng; Tang, Yuanjie; Xu, Xinhe; Lozano-Perez, Sergio; Shoji, Tetsuo
Abstract : The properties of the oxide films formed on solution-annealed and cold-worked 316L stainless steel (SS) specimens with and without charged hydrogen in deaerated pressurized water reactor primary water at 300 °C were investigated. The outer oxide layers of all specimens were composed of magnetite (Fe3 O4 ) and NiFe2 O4 . Charged hydrogen resulted in larger outer iron-bearing oxide particles forming due to hydrogen-enhanced outward diffusion of iron cations. Prior cold-work accelerates the oxidation was observed. Charged hydrogen led to local cracks in the oxide film and enhanced the penetration oxidation beneath the metal/oxide interface. The Cr-rich inner oxide layer grown on the prior cold-worked specimen with charged hydrogen was thicker than that on the cold-work specimen or the hydrogen-charged specimen, revealing the combined effects of charged hydrogen and prior cold-work on the acceleration of the oxidation process. The working mechanism of the solid-state hydrogen effect on the oxide film was discussed.